The Effect of Washing Eggs of Green Catfish (Hemibagrus nemurus) using Milk Powder Solutions on Adhesion, Fertilization Rate, Hatching Rate and Survival Rate of Larvae - Elli Syafrida Lubis; Sukendi Sukendi; Nuraini Nuraini (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Laboratory, Faculty of Fisheries and Marine, Universitas Riau, Pekanbaru. This research aims to determine the effect of Dancow full cream milk powder on eggs adhesive, fertilization rate, hatching, and the survival of Green Catfish (Hemibagrus nemurus) larvae. This experimental research used a completely randomized design with a factorial pattern (CRD) with 1 factor, 4 levels of treatment, and 3 replications. The treatment levels covered P0: No washing (Control), P1: 12 g of powdered milk + 1 g of NaCl/L of water, P2: 14 g of powdered milk + 1 g of NaCl/L of water, P3: 16 g of powdered milk + 1 g of NaCl/L of water and Washing is done for 20 minutes. The washing was performed on 1 gram of eggs or with a density of ± 570 eggs in each treatment. The best washing solution for washing eggs contained 16 g of powdered milk + 1 g of NaCl resulting in 93.57% of eggs that do not stick together (non-adhesive) and the fertilization rate reached 83.16% with the hatching rate of 86.77% and larval survival (SR 7 days) of 90.3%.